Returning Right-To-Farm Laws to Their Roots - Joseph Malanson (Washington University Law Review, 2020)
In 2014, some unlikely culprits—four chickens—generated negative headlines for then-Iowa Congressman Bruce Braley, who was in the midst of a close campaign for an open United States Senate seat. After neighbor Pauline Hampton’s chickens roamed onto the Braleys’ property, the Braleys filed a formal complaint with the neighborhood homeowners association and allegedly threatened to sue. If the Braleys had done so, questions of the scale of Hampton’s operation, how long she had had the chickens, and whether the Braleys or the chickens were in the neighborhood first would have been key considerations. Similar disputes between neighbors over agricultural land uses play out across America. This Note will focus on one attempt to manage these disputes: right-to-farm (RTF) laws. This Note proceeds in six parts. Part I continues to introduce the tension between urban and rural land uses, the importance of understanding it, and the mechanism of RTF laws that legislatures have adopted to mitigate it. Part I goes on to explain how different states design their RTF laws and considers previous scholarly treatment of RTF laws. This Note is indebted to the pre-existing literature on RTF laws, and recognizes and aims to contribute to some of these existing critiques and proposals: First, in Part II, this Note aims to add concreteness to the literature’s critique of RTF laws by focusing on two particular ways in which RTF laws have improperly expanded immunity from nuisance liability and by delving into illustrative case law demonstrating how these expansions operate in practice. In doing so, this Note will show how certain veins of RTF laws have become particularly unmoored from RTF laws’ origins as codifications of the coming-to-the-nuisance doctrine. In Part III, this Note then offers a concrete policy for returning RTF laws to their roots, ensuring agricultural operations are better held accountable for their effects on their communities. The Note cites a particular vein of RTF laws, namely Washington’s, focusing on desirable provisions, as an existing model for all states to consider adopting. It recommends revising RTF laws with even greater textual specificity than Washington’s so they only protect established agricultural operations facing urbanizing pressures. It also proposes revising RTF laws so that an operation that substantially changes its nature loses its immunity. In addition to legislative reform, this Note’s proposal also encourages jurists to consider the legislative intent and history behind RTF laws to better partner with legislatures in achieving their goals, echoing and defending Professor Andrew Reinert’s argument on judicial interpretation. This Note will then argue in Part IV that this model best accommodates the literature’s critique of RTF laws. While sharing some of these critiques, this Note approaches the literature with the perspective that reform of RTF laws is more likely than abolition. Therefore, it aims to answer but also temper some of the critiques by fleshing out two primary justifications supporting this reform: it restores the coming-to-the-nuisance doctrine’s importance in RTF laws—thus honoring parties’ expectations and property-for-personhood interests—and it reduces the economic inefficiency generated by RTF laws. In doing so, it draws on arguments from property theory, sociology, and economics to demonstrate why this Note’s proposal strikes a healthy balance between the competing policy concerns RTF laws involve. Part V considers public policy implications of implementing this reform.
Keywords: Right to farm; Nuisance; Agriculture law; Land use; Property law